Genetic evidence that promoter P2 is the physiologically significant promoter for the pyrBI operon of Escherichia coli K-12. - Liu, C (1993)
The pyrBI operon of Escherichia coli K-12 encodes the two nonidentical subunits of the pyrimidine biosynthetic enzyme aspartate transcarbamylase (ATCase). Expression of this operon is negatively regulated by pyrimidine availability primarily through UTP-sensitive transcriptional attenuation and, to a lesser extent, at the level of transcriptional initiation. Previous studies indicated that the pyrBI operon was transcribed from tandem sigma 70 promoters designated P1 and P2, with the large majority of transcription initiated at the more downstream promoter P2. To more clearly define the roles of these promoters, mutations that severely impair or inactivate individual promoters were constructed in the chromosomal pyrBI operon, and their effects on ATCase synthesis were measured. In cells grown under conditions of either pyrimidine excess or pyrimidine limitation, more than 99% of all ATCase synthesis was directed by transcripts initiated at promoter P2, indicating that it is the only physiologically significant pyrBI promoter. However, mutations that effectively inactivate promoter P1 caused a 15% reduction in ATCase levels, apparently by inhibiting transcription from promoter P2 by an unknown mechanism. Support for this explanation was provided by the demonstration that little, if any, transcriptional initiation occurred at promoter P1 in a transcriptional fusion vector whereas a high level of transcription was initiated at promoter P2 in an equivalent construction. Our results also provide evidence for pyrimidine-mediated regulation of transcriptional initiation at promoter P2 over a severalfold range and show that cells can grow reasonably well with very low levels of ATCase, apparently because of changes in the concentration of allosteric effectors that increase the specific activity of the enzyme.